EFEKTIVITAS MEDIA VIDEO DALAM MENINGKATKAN KETERAMPILAN MEMASANG JILBAB SEGI EMPAT BAGI ANAK LOW VISION X - Popy Auliya Febrita (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : This study discusses the skills to wear a rectangular hijab for grade 1 low vision children in SMALB LUKI Padang. The purpose of this study is  to prove the effectiveness of video media in enhancing the skills to wear a rectangular hijab in children with low vision. This research uses experimental approach in the form of a single subject design (SSD) with ABA design. Results from this study is effectiveness of video media in enhancing the skills to wear a rectangular hijab in children with low vision. Keyword: Keterampilan memasang jilbab segiempat